Long-Term Effects With Potential Clinical Importance of Botulinum Toxin Type-A on Mechanics of Muscles Exposed - Kaya, Cemre S.; Yılmaz, Evrim O.; Akdeniz-Doğan, Zeynep D.; Yucesoy, Can A. (Frontiers in Bioengineering and Biotechnology, 2020)
Botulinum toxin type A (BTX-A) is widely used for spasticity management and mechanically aims at reducing passive resistance at the joint and widening joint range of movement. However, recent experiments on acute BTX-A effects showed that the injected rat tibialis anterior (TA) muscle’s passive forces increased and length range of active force exertion (lrange) did not change. Additionally, BTX-A was shown to spread into non-injected muscles in the compartment and affect their mechanics. Whether those effects persist in the long-term is highly important, but unknown. The aim was to test the following hypotheses with experiments conducted in the anterior crural compartment of the rat: In the long-term, BTX-A (1) maintains lrange and (2) increases passive forces of the injected TA muscle, and (3) spreads into non-injected extensor digitorum longus (EDL) and the extensor hallucis longus (EHL) muscles, also affecting their active and passive forces. Male Wistar rats were divided into two groups: BTX-A and Control (0.1 units of BTX-A or only saline was injected into the TA). Isometric forces of the muscles were measured simultaneously one month post-injection. The targeted TA was lengthened, whereas the nontargeted EDL and EHL were kept at constant length. Hydroxyproline analysis was done to quantify changes in the collagen content of studied muscles. Two-way ANOVA (for muscle forces, factors: TA length and animal group) and unpaired-t or Mann-Whitney U test (for lrange and collagen content, where appropriate) was used for statistical analyses (P< 0.05). BTX-A caused significant effects. TA: active forces decreased (maximally by 75.2% at short and minimally by 48.3%, at long muscle lengths), lrange decreased (by 22.9%), passive forces increased (by 12.3%), and collagen content increased (approximately 3-fold). EDL and EHL: active forces decreased (up to 66.8%), passive force increased (minimally by 62.5%) and collagen content increased (approximately 2-fold). Therefore, hypothesis 1 was rejected and 2 and 3 were confirmed indicating that previously reported acute BTX-A effects persist and advance in the long-term. A narrower lrange and elevated passive resistance of the targeted muscle are unintended mechanical effects, whereas spread of BTX-A into other compartmental muscles indicates presence of also uncontrolled mechanical effects.